High-toughness and high-hardness ultra-coarse grain hard alloy with Ti (C, N) reinforced high-entropy alloy as binding phase and preparation method of high-toughness and high-hardness ultra-coarse grain hard alloy
By using Ti(C,N) enhanced high-entropy alloy as bonding phase in cemented carbide, the problem of insufficient hardness and toughness in geodesic mining and stamping molds is solved, and the super-hardness and toughness of cemented carbides is achieved. Coarse crystal carbide preparation reduces the cost of Co use and health risks.
Patent Information
- Application Number
- CN202411423423.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-10
AI Technical Summary
In the processing and manufacturing of existing cemented carbides, the hardness and toughness of geologic mining tools and cemented carbide stamping molds, and Co as a bonding phase has health risks and high costs.
Ti(C,N) enhanced high-entropy alloy is used as the bonding phase, and the cemented carbide structure is controlled by changing the content of metal elemental powder and the enhanced toughening phase Ti(C,N) to prepare high-strength and high-hard super-coarse crystal Cemented carbide, ball milling and vacuum sintering treatment using CoCuFeNiCrx high entropy alloy powder with WC and Ti(C,N) powder.
It achieves high hardness and good toughness, while reducing the cost of bonded phases, improving the mechanical properties and processing cost efficiency of the materials, and is suitable for the manufacturing of geotechnical mining tools and cemented carbide stamping molds.
Smart Images

Figure CN119287237A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cemented carbide manufacturing, and in particular relates to a high-toughness, high-hardness, ultra-coarse-grained cemented carbide with a Ti(C,N)-reinforced high-entropy alloy as a bonding phase and a preparation method thereof. Background Art
[0002] Cemented carbide is an alloy material prepared by powder sintering method with refractory metal compounds (WC, TiC, TaC, NbC, etc.) as hard phase and transition metals (Fe, Co, Ni) as bonding phase. Cemented carbide has the advantages of high strength and hardness, good wear resistance, etc. It is mainly used to make cutting tools and is widely used in the field of cutting processing.
[0003] Among them, ultra-coarse-grained cemented carbide exhibits excellent wear resistance, thermal fatigue resistance and impact resistance under extreme working conditions and continuous operation conditions, and is widely used in mining machinery, steel rolling rollers and cemented carbide stamping dies and other fields. Co is currently the most widely used cemented carbide binder phase. Compared with Fe and Ni, Co has good wettability and liquid phase sintering solubility to WC-based cemented carbide, and can thus quickly promote the densification of WC-based cemented carbide. In recent years, domestic and foreign scholars have found that Co has certain radiation, which has certain harm to human health during the production process. At the same time, Co is a national strategic resource and is expensive. Therefore, there is an urgent need for a material that can replace Co as a binder phase to prepare ultra-coarse-grained cemented carbide.
[0004] Since it was proposed, high entropy alloy has been favored by many scholars. Its original definition is that it is composed of five or more elements, the content of each element is between 5% and 35%, and it has a simple solid solution structure, such as face-centered cubic structure (FCC) and body-centered cubic structure (BCC). For example, patent publication number CN 111286664A discloses an ultrafine tungsten carbide cemented carbide with high entropy alloy as a binder phase and a preparation method thereof. This high entropy alloy is a five-component high entropy alloy of Co, Cr, Ni, Cu, and Fe. The mass percentage of the high entropy alloy accounts for 5 to 30wt.% of the total system, and the remainder is WC. First, prepare nano five-component high entropy alloy powder and refine WC powder; secondly, mix the nano five-component high entropy alloy powder and nano WC in a ball mill according to different mass ratios; pre-press the mixed powder; and anneal the pre-pressed piece. Finally, vacuum hot pressing sintering is carried out, the sintering pressure is 40-50MPa, and the sintering temperature is 1200-1400℃. Then the temperature is reduced and the pressure is released to obtain ultrafine tungsten carbide cemented carbide. After sintering, the cemented carbide sintered body is annealed. Compared with traditional alloys, high entropy alloys have five major effects, namely, high entropy effect in thermodynamics, slow diffusion effect in kinetics, lattice distortion effect in structure, "cocktail" effect in performance, and high stability effect in organization, which prompt them to form a single solid solution structure, thereby showing excellent performance, such as high hardness, corrosion resistance, oxidation resistance and other high temperature properties. However, it is still difficult to meet the processing and manufacturing of mining tools and cemented carbide stamping dies by regulating the bonding phase of high entropy alloys. Therefore, it is urgent to find a method to further improve the hardness and toughness of cemented carbide. Summary of the invention
[0005] In view of the technical problem of low hardness and toughness of high entropy alloys, the present invention proposes a high-toughness and high-hardness ultra-coarse-grained cemented carbide with Ti(C,N)-reinforced high-entropy alloy as a bonding phase and a preparation method thereof. The structure of the ultra-coarse-grained cemented carbide with high entropy alloy as a bonding phase is controlled by changing the content of metal element powder and reinforcing the toughening phase Ti(C,N), so as to prepare an ultra-coarse-grained cemented carbide with excellent mechanical properties, which is suitable for the processing and manufacturing of geological and mining tools and cemented carbide stamping dies.
[0006] In order to achieve the above object, the technical solution of the present invention is achieved as follows:
[0007] A method for preparing a high-toughness, high-hardness, ultra-coarse-grained cemented carbide with a Ti(C,N)-reinforced high-entropy alloy as a binder phase, comprising the following steps:
[0008] (1) Mixing: WC powder, Ti(C,N) powder and high entropy alloy powder are mixed and ball milled to obtain a mixed powder;
[0009] (2) Molding: pouring the mixed powder into a mold and pressing it to obtain a blank;
[0010] (3) Sintering: The blank is subjected to vacuum sintering treatment to prepare a high-toughness, high-hardness, ultra-coarse-grained cemented carbide.
[0011] The particle size of the WC powder is 4 to 10 μm; the particle size of the Ti(C, N) powder is 7 to 10 μm.
[0012] In step (1), the WC powder accounts for 70-88wt%, the high entropy alloy powder accounts for 6-15wt%, the titanium carbonitride powder accounts for 6-15wt%, and the sum of the mass percentages of each component is 100%.
[0013] The high entropy alloy powder is CoCuFeNiCr x , 0.1≤x≤3.
[0014] The high entropy alloy powder CoCuFeNiCr x It is prepared by mechanical alloying method, the steps are: five metal single substance powders of cobalt, copper, iron, nickel and chromium are mixed and then ball-milled.
[0015] The particle sizes of the five metal element powders are all 5-15 μm, CoCuFeNiCr x The atomic percentage content of each element is 5-35% respectively, and the total amount is 100%. Preferably, Co, Cu, Fe, Ni, Cr x The atomic ratio of the five elements is 2:2:2:2:1.
[0016] The ball milling process in step (1) is as follows: adding a molding agent at a ratio of 1-4% of the total weight of the ingredients, adding a wet grinding agent at a ratio of 30-50% of the total weight of the ingredients, the ball-to-material ratio is (3-15):1, the rotation speed is 50-500 r / min, and the time is 6-20 h.
[0017] The molding agent is polyethylene glycol or paraffin, and the wet grinding agent is ethanol.
[0018] The vacuum sintering conditions are: vacuum degree 10 -1 -10 -4 Pa, heating rate is 5-10℃ / min, rise to 500-1200℃, keep warm for 1-6h for degreasing, then continue to heat to 1300-1500℃, keep warm for 0.5-3h.
[0019] A high-toughness, high-hardness, ultra-coarse-grained cemented carbide with a Ti(C,N)-reinforced high-entropy alloy as a bonding phase, comprising a hard phase WC, a bonding phase high-entropy alloy and a reinforcing and toughening phase Ti(C,N); the grain size of the hard phase WC is concentrated between 4-7μm, and the average grain size of WC is 5-6μm.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention uses CoCuFeNiCr x High entropy alloy powder is used as a binding phase, replacing single cobalt as a binding phase, which can make the product have higher hardness while reducing the cost of the binding phase.
[0022] (2) CoCuFeNiCr x The high entropy alloy appropriately reduces the content of metal element Cr powder, greatly reduces the formation of BCC solid solution phase in the obtained alloy system, and its plasticity is significantly improved compared with the existing AlCoCrFeNi alloy.
[0023] (3) The present invention adopts a mechanical alloying method to perform high-energy ball milling on five kinds of elemental metal powders to obtain CoCuFeNiCr 0.5 High entropy alloy powder effectively reduces processing costs, avoids component segregation caused by existing smelting preparation processes, thereby improving the mechanical properties of the material and promoting the research and application of new cemented carbides.
[0024] (4) CoCuFeNiCr used in the present invention x High entropy alloy powder and titanium carbonitride Ti(C,N) powder are used as the binding phase and the strengthening and toughening phase respectively. The prepared ultra-coarse-grained cemented carbide has high hardness and good toughness.
[0025] (5) CoCuFeNiCr obtained by mechanical alloying 0.5 High entropy alloy powder is used as the bonding phase, WC is used as the hard phase, titanium carbonitride Ti(C,N) is added as the tough phase, and combined with the vacuum sintering process, the WC grain size can be better controlled to obtain a high-toughness, high-hardness, ultra-coarse-grained cemented carbide with Ti(C,N) reinforced high entropy alloy as the bonding phase. The grain size of the hard phase WC in the alloy is concentrated between 4-7μm, and the average grain size of WC is about 5.0-6.0μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 This is the microstructure diagram of WC-10HEA1-4Ti(C,N) ultra-coarse-grained cemented carbide.
[0028] Figure 2This is the grain size distribution diagram of WC-10HEA1-4Ti(C,N) ultra-coarse-grained cemented carbide.
[0029] Figure 3 This is the microstructure diagram of WC-10Co-4Ti(C,N) ultra-coarse-grained cemented carbide.
[0030] Figure 4 This is the grain size distribution diagram of WC-10Co-4Ti(C,N) ultra-coarse-grained cemented carbide.
[0031] Figure 5 This is the microstructure diagram of WC-10HEA1 cemented carbide.
[0032] Figure 6 It is the grain size distribution diagram of WC-10HEA1 cemented carbide.
[0033] Figure 7 WC-4Ti(C,N)-10CoCuFeNiCr 0.5 Microstructure diagram of cemented carbide.
[0034] Figure 8 WC-4Ti(C,N)-10CoCuFeNiCr 0.5 Grain size distribution diagram of cemented carbide.
[0035] Fig. 9 WC-6Ti(C,N)-10CoCuFeNiCr 0.5 Microstructure diagram of cemented carbide.
[0036] Fig.10 WC-6Ti(C,N)-10CoCuFeNiCr 0.5 Grain size distribution diagram of cemented carbide.
[0037] Fig.11 WC-8Ti(C,N)-12CoCuFeNiCr 0.5 Microstructure diagram of cemented carbide.
[0038] Fig.12 WC-8Ti(C,N)-12CoCuFeNiCr 0.5 Grain size distribution diagram of cemented carbide.
[0039] Fig.13 This is the XRD of high entropy alloy powders with different Cr contents. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example 1
[0042] An ultra-coarse-grained cemented carbide with Ti(C,N)-reinforced WC-HEA ultra-coarse-grained cemented carbide as a bonding phase, wherein the composition by mass percentage is: 86% WC (powder particle size 10.0μm), 10% HEA1 (HEA1 is CoCuFeNiCr 0.5 ), 4% Ti(C,N) (powder particle size is 9μm), and its metallographic structure is composed of WC, HEA, and Ti(C,N), among which the average size of the hard phase WC grains is 6.18μm.
[0043] The preparation steps of the above-mentioned ultra-coarse-grained cemented carbide are as follows:
[0044] (1) Five metal powders of Co, Cu, Fe, Ni and Cr were prepared in a non-equiatomic ratio of 22:22:22:22:12, and a total amount of 50 g was weighed and loaded into a ball mill. 320 ml of wet grinding medium anhydrous ethanol was added, the ball-to-material ratio was 15:1, the ball mill speed was 350 r / min, and the ball milling time was 60 h to obtain HEA1;
[0045] (2) A cemented carbide raw material with high entropy alloy powder and WC powder added is used for batching, and the composition range is as follows by mass percentage: 86% WC with a powder particle size of 10.0 μm, 4% Ti (C, N) with a powder particle size of 9 μm, and 10% CoCuFeNiCr 0.5 , after mixing the above raw materials, add them into a planetary ball mill for wet grinding, add 320 ml of wet grinding medium anhydrous ethanol, the ball-to-material ratio is 15:1, and the molding agent polyethylene glycol is added at a ratio of 4% of the total weight of the ingredients, the ball milling speed is 80 r / min, and the ball milling time is 12 h;
[0046] (3) After the ball milling, the powder slurry is vacuum dried, sieved and stored for later use. 8 g of the mixed powder is weighed and poured into a cemented carbide mold, and a single axial pressure of 6 t is applied to obtain a blank;
[0047] (4) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -1Pa, the temperature was raised to 600℃ and kept for 3h for degreasing, then continued to rise to 800℃, 1000℃, 1200℃, and kept at these three temperatures for 30min respectively, and continued to rise to the sintering temperature of 1450℃ and kept for 1h for sintering. After the end of the heat preservation, the furnace was cooled to room temperature to obtain WC-10HEA1-4Ti(C,N) ultra-coarse-grained cemented carbide. The average grain size of WC grains was about 6.18μm, and the hardness of the cemented carbide was about HV 30 1175, fracture toughness is about 21MPa·m 1 / 2 .
[0048] Figure 1 This is the microstructure diagram of WC-10HEA1-4Ti(C,N) ultra-coarse-grained cemented carbide. From the figure, we can see that the white phase is WC phase, and the black phase between the white WC phase is the bonding phase HEA. The WC grains of WC-10HEA1-4Ti(C,N) ultra-coarse-grained cemented carbide are mostly trapezoidal and other irregular quadrilaterals, and the grain distribution is relatively uniform.
[0049] Figure 2 This is the grain size distribution diagram of WC-10HEA1-4Ti(C,N) ultra-coarse-grained cemented carbide. The WC grains of the cemented carbide are mainly distributed in the range of 4 to 8 μm. The average grain size of the cemented carbide prepared by comparison 1 is 6.18 μm.
[0050] Comparative Example 1
[0051] An ultra-coarse-grained cemented carbide with Ti(C,N)-reinforced WC-Co ultra-coarse-grained cemented carbide as a bonding phase, wherein the composition by mass percentage is: 86% WC (powder particle size is 10.0μm), 10% Co (powder particle size is 0.8μm), 4% Ti(C,N) (powder particle size is 9μm), and the metallographic structure is composed of WC, Co, and Ti(C,N) as constituent phases, wherein the average size of the hard phase WC grains is 7.72μm.
[0052] The preparation steps of the above-mentioned ultra-coarse-grained cemented carbide are as follows:
[0053] (1) Take WC powder, Co powder and Ti (C, N) powder, weigh a total of 50g, put it into a ball mill, add 320ml of wet grinding medium anhydrous ethanol, the ball-to-material ratio is 15:1, and the molding agent polyethylene glycol is added at a ratio of 4% of the total weight of the ingredients. The ball mill speed is 80r / min and the ball milling time is 12h;
[0054] (2) After the ball milling, the powder slurry is vacuum dried, sieved and stored for later use. 8 g of the mixed powder is weighed and poured into a cemented carbide mold, and a single axial pressure of 6 t is applied to obtain a blank;
[0055] (3) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -1 Pa, the temperature was raised to 600℃ and kept for 3h for degreasing, then continued to rise to 800℃, 1000℃, 1200℃, and kept at these three temperatures for 30min respectively, and continued to rise to the sintering temperature of 1450℃ and kept for 1h for sintering. After the end of the heat preservation, the furnace was cooled to room temperature to obtain WC-10Co-4Ti(C,N) ultra-coarse-grained cemented carbide. The average grain size of WC grains was about 7.72μm, and the hardness of the cemented carbide was about HV 30 1125, fracture toughness is about 19MPa·m 1 / 2 .
[0056] Figure 3 It is the microstructure diagram of WC-10Co-4Ti(C,N) ultra-coarse-grained cemented carbide. It can be seen from the figure that the WC grains of WC-10Co-4Ti(C,N) ultra-coarse-grained cemented carbide are mostly triangles, irregular quadrilaterals and trapezoids, the grain distribution is relatively uneven and there are larger WC grains, which will cause the local hardness of the prepared cemented carbide to be low, hindering the effective growth of WC grains.
[0057] Figure 4 The figure is a grain size distribution diagram of WC-10Co-4Ti(C,N) ultra-coarse-grained cemented carbide. The WC grains of the cemented carbide are mainly distributed in the range of 5 to 10 μm, and the average grain size of the cemented carbide prepared in Comparative Example 1 is 7.72 μm. The increase in the particle size of the WC powder leads to a decrease in the hardness of the cemented carbide, which reduces the mechanical properties of the cemented carbide to a certain extent.
[0058] Comparative Example 2
[0059] An ultra-coarse-grained cemented carbide with WC-HEA ultra-coarse-grained cemented carbide as a bonding phase, wherein the composition by mass percentage is: 90% WC (powder particle size 10.0 μm), 10% HEA1 (HEA1 is CoCuFeNiCr 0.5 ), its metallographic structure is composed of WC and HEA, among which the average size of the hard phase WC grains is 6.08μm.
[0060] The preparation steps of the above-mentioned ultra-coarse-grained cemented carbide are as follows:
[0061] (1) Five metal powders of Co, Cu, Fe, Ni and Cr were prepared in a non-equiatomic ratio of 22:22:22:22:12, and a total amount of 50 g was weighed and loaded into a ball mill. 320 ml of wet grinding medium anhydrous ethanol was added, the ball-to-material ratio was 15:1, the ball mill speed was 350 r / min, and the ball milling time was 60 h to obtain HEA1;
[0062] (2) A cemented carbide raw material with high entropy alloy powder and WC powder added is used for batching, and the composition range is as follows by mass percentage: 90% WC with a powder particle size of 10.0 μm and 10% CoCuFeNiCr 0.5 , after mixing the above raw materials, add them into a planetary ball mill for wet grinding, add 320 ml of wet grinding medium anhydrous ethanol, the ball-to-material ratio is 15:1, and the molding agent polyethylene glycol is added at a ratio of 4% of the total weight of the ingredients, the ball milling speed is 80 r / min, and the ball milling time is 12 h;
[0063] (3) After the ball milling, the powder slurry is vacuum dried, sieved and stored for later use. 8 g of the mixed powder is weighed and poured into a cemented carbide mold, and a single axial pressure of 6 t is applied to obtain a blank;
[0064] (4) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -1 Pa, the temperature was raised to 600℃ and kept for 3h for degreasing, then continued to rise to 800℃, 1000℃, 1200℃, and kept at these three temperatures for 30min respectively, and continued to rise to the sintering temperature of 1450℃ and kept for 1h for sintering. After the end of the heat preservation, it was cooled to room temperature with the furnace to obtain WC-10HEA1 ultra-coarse-grained cemented carbide. The average grain size of WC grains was about 6.08μm, and the hardness of the cemented carbide was about HV 30 1175, fracture toughness is about 21MPa·m 1 / 2 .
[0065] Figure 5 This is the microstructure diagram of WC-10HEA1 ultra-coarse-grained cemented carbide. From the figure, it can be seen that the white phase is WC phase, and the black phase between WC grains is high entropy alloy (HEA), which is marked by white arrows in the figure. WC grains are mostly irregular quadrilaterals, the edges and corners of the grains are relatively smooth, and the grain aggregation phenomenon is obvious.
[0066] Figure 6 This is the grain size distribution diagram of WC-10HEA1 ultra-coarse-grained cemented carbide. The main distribution range of the prepared WC grain size is between 4 and 6μm. The average grain size of WC is 6.08μm.
[0067] Example 2
[0068] A high-toughness, high-hardness, ultra-coarse-grained cemented carbide with Ti(C,N)-reinforced high-entropy alloy as a bonding phase, wherein the composition by mass percentage is: 84% WC (powder particle size 10.0μm), 6% Ti(C,N) (powder particle size 10.0μm), 10% CoCuFeNiCr 0.5 Its metallographic structure is WC, Ti(C,N) and CoCuFeNiCr 0.5It is the constituent phase, in which the average size of the hard phase WC grains is 5.18μm.
[0069] The preparation steps of the above-mentioned high-toughness, high-hardness and ultra-coarse-grained cemented carbide are as follows:
[0070] (1) Five metal powders of Co, Cu, Fe, Ni and Cr were prepared in a non-equiatomic ratio of 22:22:22:22:12. A total of 50 g was weighed and loaded into a ball mill. 320 ml of wet grinding medium anhydrous ethanol was added. The ball-to-material ratio was 15:1, the ball mill speed was 350 r / min, and the ball milling time was 60 h.
[0071] (2) A cemented carbide raw material with high entropy alloy powder and WC powder added is used for batching, and the composition range is as follows by mass percentage: 86% WC with a powder particle size of 10.0 μm, 4% Ti (C, N) with a powder particle size of 10.0 μm, and 10% CoCuFeNiCr 0.5 , the above raw materials are mixed and added into a planetary ball mill for wet grinding, the ball-to-material ratio is 5:1, the wet grinding medium is alcohol, the molding agent polyethylene glycol is added at a ratio of 4% of the total weight of the ingredients, the speed is 100r / min, the wet grinding time is 15h, and then the slurry is vacuum dried, sieved and stored for later use, 8g of the mixed powder is weighed and poured into a cemented carbide mold, and a single axial pressure of 7t is applied to obtain a blank;
[0072] (3) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -1 Pa, the temperature was raised to 750 ° C and kept for 4 hours for degreasing, and then the temperature was continued to rise to 1370 ° C and kept for 2.5 hours for sintering. After the end of the heat preservation, the furnace was cooled to room temperature to obtain a high-toughness, high-hardness, ultra-coarse-grained cemented carbide with Ti (C, N) reinforced high-entropy alloy as the binder phase. The average grain size of WC grains was about 5.18 μm, and the hardness of the cemented carbide was about HV 30 1300, fracture toughness is about 23MPa·m 1 / 2 .
[0073] Figure 7 WC-4Ti(C,N)-10CoCuFeNiCr 0.5 The microstructure diagram of cemented carbide shows that WC grains are mostly irregular spherical. A "core ring" structure with a black phase surrounded by a gray phase appears in the alloy structure. The black core is Ti(C,N), and the surrounding gray phase is (W,Ti)(C,N) phase.
[0074] Figure 8 WC-4Ti(C,N)-10CoCuFeNiCr 0.5The grain size distribution diagram of cemented carbide shows that the WC grains of cemented carbide are mainly distributed in the range of 3 to 7 μm, and the average grain size of the cemented carbide prepared in Example 2 is 5.18 μm.
[0075] Example 3
[0076] A high-toughness, high-hardness, ultra-coarse-grained cemented carbide with Ti(C,N)-reinforced high-entropy alloy as a binder phase, the composition of which is as follows by mass percentage: 84% WC (powder particle size 15.0μm), 6% Ti(C,N) (powder particle size 8.0μm), 10% CoCuFeNiCr 0.5 Its metallographic structure is WC, Ti(C,N) and CoCuFeNiCr 0.5 It is the constituent phase, among which the average size of the hard phase WC grains is 5.17μm.
[0077] The preparation steps of the above-mentioned high-toughness, high-hardness and ultra-coarse-grained cemented carbide are as follows:
[0078] (1) Five metal powders of Co, Cu, Fe, Ni and Cr were prepared in a non-equiatomic ratio of 22:22:22:22:12, and a total amount of 50 g was weighed and loaded into a ball mill. 220 ml of anhydrous ethanol as a wet grinding medium was added, and a molding agent of polyethylene glycol was added at a ratio of 4% of the total weight of the ingredients. The ball-to-material ratio was 10:1, the ball mill speed was 300 r / min, and the ball milling time was 50 h.
[0079] (2) A cemented carbide raw material with high entropy alloy powder and WC powder added is used for batching, and the composition range is as follows: 84% 15.0 μm WC, 6% 8.0 μm Ti (C, N) and 10% CoCuFeNiCr by mass percentage. 0.5 , the above raw materials are mixed and added into a planetary ball mill for wet grinding, the ball-to-material ratio is 3:1, the wet grinding medium is alcohol, the rotation speed is 80r / min, the wet grinding time is 12h, and then the slurry is vacuum dried, sieved and stored for later use, 7g of the mixed powder is weighed and poured into a cemented carbide mold, and a single axial pressure of 6t is applied to obtain a blank;
[0080] (3) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -1 Pa, the temperature was raised to 600 ° C and kept for 3 hours for degreasing, and then continued to rise to 1400 ° C and kept for 1 hour for sintering. After the end of the heat preservation, the furnace was cooled to room temperature to obtain a high-toughness, high-hardness, ultra-coarse-grained cemented carbide with Ti (C, N) reinforced high-entropy alloy as the binder phase. The average grain size of WC grains was about 5.17 μm, and the hardness of the cemented carbide was about HV 30 1200, fracture toughness is about 22MPa·m 1 / 2 .
[0081] Fig. 9 WC-6Ti(C,N)-10CoCuFeNiCr 0.5 Microstructure diagram of cemented carbide.
[0082] Fig.10 WC-6Ti(C,N)-10CoCuFeNiCr 0.5 The grain size distribution diagram of cemented carbide shows that the average grain size of the cemented carbide prepared in Example 3 is 5.17 μm.
[0083] Example 4
[0084] A high-toughness, high-hardness, ultra-coarse-grained cemented carbide with Ti(C,N)-reinforced high-entropy alloy as a binder phase, the composition of which is as follows by mass percentage: 80% WC (powder particle size 15.0μm), 8% Ti(C,N) (powder particle size 9.0μm), 12% CoCuFeNiCr 0.5 Its metallographic structure is WC, Ti(C,N) and CoCuFeNiCr 0.5 It is the constituent phase, among which the average size of the hard phase WC grains is 5.24μm.
[0085] The preparation steps of the above-mentioned high-toughness, high-hardness and ultra-coarse-grained cemented carbide are as follows:
[0086] (1) Five metal powders of Co, Cu, Fe, Ni and Cr were prepared in a non-equiatomic ratio of 22:22:22:22:12, and a total amount of 50 g was weighed and loaded into a ball mill. 120 ml of anhydrous ethanol as a wet grinding medium was added, and a molding agent of polyethylene glycol was added at a ratio of 4% of the total weight of the ingredients. The ball-to-material ratio was 5:1, the ball mill speed was 400 r / min, and the ball milling time was 55 h.
[0087] (2) A cemented carbide raw material with high entropy alloy powder and WC powder added is used for batching, and the composition range is as follows by mass percentage: 80% 15.0 μm WC, 8% Ti (C, N) (powder particle size is 9.0 μm) and 12% CoCuFeNiCr 0.5 , the above raw materials are mixed and added into a planetary ball mill for wet grinding, the ball-to-material ratio is 7:1, the wet grinding medium is alcohol, the rotation speed is 100r / min, the wet grinding time is 18h, and then the slurry is vacuum dried, sieved and stored for later use, 7g of the mixed powder is weighed and poured into a cemented carbide mold, and a single axial pressure of 6t is applied to obtain a blank;
[0088] (3) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -1Pa, the temperature was raised to 700 ° C and kept for 6 hours for degreasing, and then the temperature was further raised to 1450 ° C and kept for 1.5 hours for sintering. After the end of the heat preservation, the furnace was cooled to room temperature to obtain a high-toughness, high-hardness, ultra-coarse-grained cemented carbide with Ti (C, N) reinforced high-entropy alloy as the binder phase. The average grain size of WC grains was about 5.24 μm, and the hardness of the cemented carbide was about HV 30 1250, fracture toughness is about 23MPa·m 1 / 2 .
[0089] Fig.11 WC-8Ti(C,N)-12CoCuFeNiCr 0.5 Microstructure diagram of cemented carbide.
[0090] Fig.12 WC-8Ti(C,N)-12CoCuFeNiCr 0.5 The grain size distribution diagram of cemented carbide shows that the average grain size of the cemented carbide prepared in Example 4 is 5.24 μm.
[0091] Example 5
[0092] An ultra-coarse-grained cemented carbide with Ti(C,N)-reinforced WC-HEA ultra-coarse-grained cemented carbide as a bonding phase, wherein the composition by mass percentage is: 80% WC (powder particle size 7.0μm), 15% HEA2 (HEA2 is CoCuFeNiCr 1.0 ), 5% Ti(C,N) (powder particle size is 8μm), and its metallographic structure is composed of WC, HEA, and Ti(C,N), among which the average size of the hard phase WC grains is 6.21μm.
[0093] The preparation steps of the above-mentioned ultra-coarse-grained cemented carbide are as follows:
[0094] (1) Five metal powders of Co, Cu, Fe, Ni and Cr were prepared in a non-equiatomic ratio of 22:22:22:22:22, and a total amount of 50 g was weighed and loaded into a ball mill. 320 ml of wet grinding medium anhydrous ethanol was added, the ball-to-material ratio was 15:1, the ball mill speed was 350 r / min, and the ball milling time was 60 h to obtain HEA2;
[0095] (2) A cemented carbide raw material with high entropy alloy powder and WC powder added is used for batching, and the composition range is as follows by mass percentage: 80% WC with a powder particle size of 7.0 μm, 5% Ti (C, N) with a powder particle size of 8 μm, and 15% CoCuFeNiCr 1.0, after mixing the above raw materials, add them into a planetary ball mill for wet grinding, add 320 ml of wet grinding medium anhydrous ethanol, the ball-to-material ratio is 10:1, and the molding agent polyethylene glycol is added at a ratio of 4% of the total weight of the ingredients, the ball milling speed is 500 r / min, and the ball milling time is 6 hours;
[0096] (3) After the ball milling, the powder slurry is vacuum dried, sieved and stored for later use. 8 g of the mixed powder is weighed and poured into a cemented carbide mold, and a single axial pressure of 6 t is applied to obtain a blank;
[0097] (4) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -2 Pa, the temperature was raised to 600℃ and kept for 3h for degreasing, then continued to rise to 500℃, 1000℃, 1200℃, and kept at these three temperatures for 30min respectively, and continued to rise to the sintering temperature of 1300℃ and kept for 1h for sintering. After the end of the heat preservation, the furnace was cooled to room temperature to obtain WC-10HEA2-4Ti(C,N) ultra-coarse-grained cemented carbide. The average grain size of WC grains was about 6.21μm, and the hardness of the cemented carbide was about HV 30 1155, fracture toughness is about 20MPa·m 1 / 2 .
[0098] Example 6
[0099] An ultra-coarse-grained cemented carbide with Ti(C,N)-reinforced WC-HEA ultra-coarse-grained cemented carbide as a bonding phase, the composition of which is as follows by mass percentage: 70% WC (powder particle size 4.0μm), 15% HEA3 (HEA3 is CoCuFeNiCr 1.5 ), 15% Ti(C,N) (powder particle size is 7μm), and its metallographic structure is composed of WC, HEA, and Ti(C,N), among which the average size of the hard phase WC grains is 5.85μm.
[0100] The preparation steps of the above-mentioned ultra-coarse-grained cemented carbide are as follows:
[0101] (1) Five metal powders of Co, Cu, Fe, Ni and Cr were prepared in a non-equiatomic ratio of 22:22:22:22:35, and a total amount of 50 g was weighed and loaded into a ball mill. 320 ml of wet grinding medium anhydrous ethanol was added, the ball-to-material ratio was 15:1, the ball mill speed was 350 r / min, and the ball milling time was 60 h to obtain HEA3;
[0102] (2) A cemented carbide raw material with high entropy alloy powder and WC powder added is used for batching, and the composition range is as follows by mass percentage: 70% WC with a powder particle size of 4.0 μm, 15% Ti (C, N) with a powder particle size of 8 μm, and 15% CoCuFeNiCr 1.5, after mixing the above raw materials, add them into a planetary ball mill for wet grinding, add 320 ml of wet grinding medium anhydrous ethanol, the ball-to-material ratio is 3:1, and the molding agent paraffin is added at a ratio of 1% of the total weight of the ingredients, the ball mill speed is 50r / min, and the ball milling time is 20h;
[0103] (3) After the ball milling, the powder slurry is vacuum dried, sieved and stored for later use. 8 g of the mixed powder is weighed and poured into a cemented carbide mold, and a single axial pressure of 6 t is applied to obtain a blank;
[0104] (4) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -4 Pa, the temperature was raised to 500°C and kept for 3 hours for degreasing, then the temperature was continued to be raised to 800°C, 1000°C, and 1200°C, and kept at these three temperatures for 30 minutes respectively, and then the temperature was continued to be raised to the sintering temperature of 1500°C and kept for 30 minutes for sintering. After the end of the heat preservation, the furnace was cooled to room temperature to obtain WC-10HEA3-4Ti(C,N) ultra-coarse-grained cemented carbide, the average grain size of WC grains was about 5.85μm, and the hardness of the cemented carbide was about HV 30 1258, fracture toughness is about 22MPa·m 1 / 2 .
[0105] Example 7
[0106] An ultra-coarse-grained cemented carbide with Ti(C,N)-reinforced WC-HEA ultra-coarse-grained cemented carbide as a bonding phase, the composition of which is as follows by mass percentage: 86% WC (powder particle size 10.0μm), 10% HEA4 (HEA4 is CoCuFeNiCr 2.0 ), 4% Ti(C,N) (powder particle size is 9μm), and its metallographic structure is composed of WC, HEA, and Ti(C,N), among which the average size of the hard phase WC grains is 6.37μm.
[0107] The preparation steps of the above-mentioned ultra-coarse-grained cemented carbide are as follows:
[0108] (1) Five metal powders of Co, Cu, Fe, Ni and Cr were prepared in a non-equiatomic ratio of 22:22:22:22:44, and a total amount of 50 g was weighed and loaded into a ball mill. 320 ml of wet grinding medium anhydrous ethanol was added, the ball-to-material ratio was 15:1, the ball mill speed was 350 r / min, and the ball milling time was 60 h to obtain HEA1;
[0109] (2) A cemented carbide raw material with high entropy alloy powder and WC powder added is used for batching, and the composition range is as follows by mass percentage: 86% WC with a powder particle size of 10.0 μm, 4% Ti (C, N) with a powder particle size of 9 μm, and 10% CoCuFeNiCr 2.0, after mixing the above raw materials, add them into a planetary ball mill for wet grinding, add 320 ml of wet grinding medium anhydrous ethanol, the ball-to-material ratio is 15:1, and the molding agent polyethylene glycol is added at a ratio of 4% of the total weight of the ingredients, the ball milling speed is 80 r / min, and the ball milling time is 12 h;
[0110] (3) After the ball milling, the powder slurry is vacuum dried, sieved and stored for later use. 8 g of the mixed powder is weighed and poured into a cemented carbide mold, and a single axial pressure of 6 t is applied to obtain a blank;
[0111] (4) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -1 Pa, the temperature was raised to 600℃ and kept for 3h for degreasing, then continued to rise to 800℃, 1000℃, 1200℃, and kept at these three temperatures for 30min respectively, and continued to rise to the sintering temperature of 1450℃ and kept for 1h for sintering. After the end of the heat preservation, the furnace was cooled to room temperature to obtain WC-10HEA4-4Ti(C,N) ultra-coarse-grained cemented carbide. The average grain size of WC grains was about 6.37μm, and the hardness of the cemented carbide was about HV 30 1121, fracture toughness is about 18MPa·m 1 / 2 .
[0112] Example 8
[0113] An ultra-coarse-grained cemented carbide with Ti(C,N)-reinforced WC-HEA ultra-coarse-grained cemented carbide as a bonding phase, the composition of which is as follows by mass percentage: 86% WC (powder particle size 10.0μm), 10% HEA5 (HEA5 is CoCuFeNiCr 2.5 ), 4% Ti(C,N) (powder particle size is 9μm), and its metallographic structure is composed of WC, HEA, and Ti(C,N), among which the average size of the hard phase WC grains is 6.49μm.
[0114] The preparation steps of the above-mentioned ultra-coarse-grained cemented carbide are as follows:
[0115] (1) Five metal powders of Co, Cu, Fe, Ni and Cr were prepared in a non-equiatomic ratio of 22:22:22:22:55, and a total amount of 50 g was weighed and loaded into a ball mill. 320 ml of wet grinding medium anhydrous ethanol was added, the ball-to-material ratio was 15:1, the ball mill speed was 350 r / min, and the ball milling time was 60 h to obtain HEA5;
[0116] (2) A cemented carbide raw material with high entropy alloy powder and WC powder added is used for batching, and the composition range is as follows by mass percentage: 86% WC with a powder particle size of 10.0 μm, 4% Ti (C, N) with a powder particle size of 9 μm, and 10% CoCuFeNiCr 2.5, after mixing the above raw materials, add them into a planetary ball mill for wet grinding, add 320 ml of wet grinding medium anhydrous ethanol, the ball-to-material ratio is 15:1, and the molding agent polyethylene glycol is added at a ratio of 4% of the total weight of the ingredients, the ball milling speed is 80 r / min, and the ball milling time is 12 h;
[0117] (3) After the ball milling, the powder slurry is vacuum dried, sieved and stored for later use. 8 g of the mixed powder is weighed and poured into a cemented carbide mold, and a single axial pressure of 6 t is applied to obtain a blank;
[0118] (4) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -1 Pa, the temperature was raised to 600℃ and kept for 3h for degreasing, then continued to rise to 800℃, 1000℃, 1200℃, and kept at these three temperatures for 30min respectively, and continued to rise to the sintering temperature of 1450℃ and kept for 1h for sintering. After the end of the heat preservation, the furnace was cooled to room temperature to obtain WC-10HEA5-4Ti(C,N) ultra-coarse-grained cemented carbide. The average grain size of WC grains was about 6.49μm, and the hardness of the cemented carbide was about HV 30 1135, fracture toughness is about 19MPa·m 1 / 2 .
[0119] Fig.13 CoCuFeNiCr prepared by Example 1 and Example 5-8 x (x=0.5, 1.0, 1.5, 2.0, 2.5) XRD patterns of high entropy alloy powders, HEA1 is CoCuFeNiCr 0.5 HEA2 is CoCuFeNiCr 1.0 HEA3 is CoCuFeNiCr 1.5 、HEA4 is CoCuFeNiCr 2.0 、MEA is CoCuFeNiCr 2.5 ).from Fig.13 It can be seen that alloying elements with lower valence electron concentration in the mixed powder system are beneficial to improving the strength of the prepared alloy, while alloying elements with higher valence electron concentration are beneficial to improving the plasticity of the prepared alloy.
[0120] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-toughness, high-hardness, ultra-coarse-grained cemented carbide with Ti(C,N)-reinforced high-entropy alloy as a binder phase, characterized in that: The following steps are involved: (1) Mixing: WC powder, Ti(C,N) powder and high entropy alloy powder are mixed and ball milled to obtain a mixed powder; (2) Molding: pouring the mixed powder into a mold and pressing it to obtain a blank; (3) Sintering: The blank is subjected to vacuum sintering treatment to prepare a high-toughness, high-hardness, ultra-coarse-grained cemented carbide.
2. The method for preparing a high-toughness, high-hardness, ultra-coarse-grained cemented carbide with a Ti(C,N)-reinforced high-entropy alloy as a binder phase according to claim 1, characterized in that: The particle size of the WC powder is 4 to 10 μm; the particle size of the Ti(C, N) powder is 7 to 10 μm.
3. The method for preparing a high-toughness, high-hardness, ultra-coarse-grained cemented carbide with a Ti(C,N)-reinforced high-entropy alloy as a binder phase according to claim 2, characterized in that: In the step (1), the WC powder accounts for 70-88wt%, the high entropy alloy powder accounts for 6-15wt%, the titanium carbonitride powder accounts for 4-15wt%, and the sum of the mass percentages of each component is 100%.
4. The method for preparing a high-toughness, high-hardness, ultra-coarse-grained cemented carbide with a Ti(C,N)-reinforced high-entropy alloy as a binder phase according to claim 1, characterized in that: The high entropy alloy powder is CoCuFeNiCr x , 0.1≤x≤3.
5. The method for preparing a high-toughness, high-hardness, ultra-coarse-grained cemented carbide with a Ti(C,N)-reinforced high-entropy alloy as a binder phase according to claim 4, characterized in that: The high entropy alloy powder CoCuFeNiCr x It is prepared by mechanical alloying method, the steps are: five metal single substance powders of cobalt, copper, iron, nickel and chromium are mixed and then ball-milled.
6. The method for preparing a high-toughness, high-hardness, ultra-coarse-grained cemented carbide with a Ti(C,N)-reinforced high-entropy alloy as a binder phase according to claim 5, characterized in that: The particle sizes of the five metal element powders are all 5-15 μm, CoCuFeNiCr x The atomic percentage content of each element is 5-35%.
7. The method for preparing a high-toughness, high-hardness, ultra-coarse-grained cemented carbide with a Ti(C,N)-reinforced high-entropy alloy as a binder phase according to claim 1, characterized in that: The ball milling process in step (1) is as follows: adding a molding agent at a ratio of 1-4% of the total weight of the ingredients, adding a wet grinding agent at a ratio of 30-50% of the total weight of the ingredients, the ball-to-material ratio is (3-15):1, the rotation speed is 50-500 r / min, and the time is 6-20 h.
8. The method for preparing a high-toughness, high-hardness, ultra-coarse-grained cemented carbide with Ti(C,N)-reinforced high-entropy alloy as a binder phase according to claim 7, characterized in that: The molding agent is polyethylene glycol or paraffin, and the wet grinding agent is ethanol.
9. The method for preparing a high-toughness, high-hardness, ultra-coarse-grained cemented carbide with a Ti(C,N)-reinforced high-entropy alloy as a binder phase according to claim 1, characterized in that: The vacuum sintering conditions are: vacuum degree 10 -1 -10 -4 Pa, heating rate is 5-10℃ / min, rise to 500-1200℃, keep warm for 1-6h for degreasing, then continue to heat to 1300-1500℃, keep warm for 0.5-3h.
10. A high-toughness, high-hardness, ultra-coarse-grained cemented carbide with a Ti(C,N)-reinforced high-entropy alloy as a binder phase prepared by the method according to any one of claims 1 to 9, characterized in that: It includes a hard phase WC, a bonding phase high entropy alloy and a strengthening and toughening phase Ti(C,N); the grain size of the hard phase WC is distributed between 4-7μm, and the average grain size of WC is 5-6μm.
Citation Information
Patent Citations
Ultrafine tungsten carbide hard alloy with high-entropy alloy as binding phase and preparation method thereof
CN111286664A